2019
DOI: 10.1021/acsomega.9b01139
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Functionalization of Porous Zr-Diaminostilbenedicarboxylate Metal–Organic Framework for Storage and Stable Delivery of Ibuprofen

Abstract: A stable porous metal–organic framework (MOF), Zr-diaminostilbenedicarboxylate (Zr-DASDCA), was synthesized and modified with oxalyl chloride (OC) or terephthaloyl chloride (TC) to introduce various functional groups onto the Zr-DASDCA. Both pristine and functionalized Zr-DASDCAs, together with activated carbon, were used as a potential carrier for ibuprofen (IBU) storage and delivery. Zr-DASDCAs, especially the modified ones (OC-Zr-DASDCA and TC-Zr-DASDCA), showed competitive results in IBU delivery. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 71 publications
2
17
0
Order By: Relevance
“…As such, mixed release patterns are likely the result of having no burst in the first stage, with a slight increase in Ru or Pip release at the second stage. The observation of a two-stage pattern is in agreement with previous reports, including release of ibuprofen from various MOFs (Silva et al, 2016 ; Rojas et al, 2018 ; Sarker et al, 2019 ; Pham et al, 2020 ), 5-fluorouracil from Mg-MOFs (Hu et al, 2020 ), caffeine from ZrMOFs (Sarker & Jhung, 2019 ), and DOX from a zeolitic imidazolate MOF (Bi et al, 2018 ).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…As such, mixed release patterns are likely the result of having no burst in the first stage, with a slight increase in Ru or Pip release at the second stage. The observation of a two-stage pattern is in agreement with previous reports, including release of ibuprofen from various MOFs (Silva et al, 2016 ; Rojas et al, 2018 ; Sarker et al, 2019 ; Pham et al, 2020 ), 5-fluorouracil from Mg-MOFs (Hu et al, 2020 ), caffeine from ZrMOFs (Sarker & Jhung, 2019 ), and DOX from a zeolitic imidazolate MOF (Bi et al, 2018 ).…”
Section: Resultssupporting
confidence: 91%
“…This shift is connected to the decomposition/volatilization of both natural agents used. Of note, the shifted peaks in the nanoformulations appeared to correspond to those for free Ru and Pip, confirming the successful loading process for either single or double drug loading (Cunha et al, 2013a , b ; Sarker & Jhung, 2019 ; Sarker et al, 2019 ).…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…However, this method has several stringent requirements to ensure the stability of the MOFs. Sarker et al [25] synthesised a stable, porous MOF named Zr-diaminostyrene dicarboxylic acid (Zr-DASDCA). The MOF was modified with oxaloyl chloride (OC) or p-benzoyl chloride (TC) after its synthesis to introduce different functional groups into Zr-DASDCA.…”
Section: Synthesis and Functionalisation Of Mofsmentioning
confidence: 99%
“…For example, a Zr‐MOF modified with oxalyl chloride or terephthaloyl chloride (i.e., OC‐Zr‐DASDCA and TC‐Zr‐DASDCA, respectively) resulted in nearly 100% release of ibuprofen in phosphate‐buffered saline (PBS) at pH 7.4 for 10 days and 45% at pH 3.0. [ 26 ] Lestari et al used a [Zn 3 (BTC) 2 ]‐based matrix, and their results showed the presence of the matrix reduced the rate of ibuprofen release by 33.4%. Other MOFs that have been developed for ibuprofen encapsulation are [Zn 2 (bdc) 2 (dabco)], which was synthesized in situ and has a drug release capability up to 80% after 12 days, [ 27 ] and MIL‐53(Fe), which was studied by Horcajada et al and had an adsorption ability of 0.21 g of ibuprofen in 1 g of MOF in simulated body fluid at 37°C for 3 weeks.…”
Section: Introductionmentioning
confidence: 99%